Adsorbers for KMnO 4 and L-Ascorbic Acid in the Active Packaging to Prolong the Shelve-Life and Maintain the Quality of Lanzone (Lansium domesticum Corr.)Fruits - Soesiladi E Widodo (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2005)
To develop an active packaging of lanzone (Lansium domisticum Corr.) Fruits, KmnO4 as an ethylene scavenger and L-ascorbic acid as an oxygent scavenger were inserted into packaging. As direct contact of KmnO4 with agricultural product was not recommended and due to the liquid characteristic of both scavenger was carried out. This research was aimed at finding out the best adsorbers for KmnO4, L-ascorbic acid, and their combination in an active packaging to prolog the shelve-life and to maintain the quality of lanzone fruits. The result showed that 1) among the four adsorbers tested, pumice could was the best alternative as a KmnO4 or L-ascorbic acid adsorbers, and 2)) spon and pumice were the best alternative adsorber for the combination of KmnO4 or L-ascorbic acid. Both adsorber were effective in prolonging the shelve-live (8-11 days longer than with out packaging and as good as using silica gel and vermiculite) and maintaining the quality of lanzone fruits. Key word: lanzone, duku, active packaging, KmnO4, L-ascorbic acid.